ANALISIS KARAKTERISTIK MUTU NATA DE LERI DENGAN VARIASI KONSENTRASI GULA PASIR SEBAGAI SUMBER KARBON - Andi Maryam (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Nata de leri is nata that is processed using rice washing water which has the potential to become a fiber-rich snack. The purpose of this study was to determine the yield, thickness, and fiber content of nata de leri with variations in the concentration of granulated sugar as a carbon source (ie 5% and 10% granulated sugar). The results showed that Nata de leri with 5% sugar concentration produced 66.14% yield, 0.62 cm thickness, and 14.21% fiber content, while the 5% granulated sugar treatment had 45.31% yield, thickness 0, 67 cm, and 12.20% fiber content.